Optimal location of brake pad for reduction of temperature deviation on brake disc during high-energy braking - Hong, Heerok; Kim, Gyeongpil; Lee, Hoyong; Kim, Jaesik; Lee, Dasom; Kim, Minsoo; Suh, Myungwon; Lee, Junghwan (Journal of mechanical science and technology, 2021)
During the braking process, frictional heat generated between a disc and a pad can lead to high temperatures. The location of friction blocks on the brake pad can lead directly to differences in friction contact time and friction speed at each point on the brake disc surface, this can lead to non-uniform temperature distribution on the brake disc surface. In this paper, the optimum design for friction blocks on a brake pad is investigated using the design of experiments (DOE) of Taguchi approach and response surface method (RSM) with an aim to minimize the deviation in the rate of friction heating in each area along the radial direction of brake disc. 18 design variables on 2 levels are adjusted. A table of orthogonal arrays, L32 (218), is used. Finite element analysis (FEA) is performed to analyze the mean squared error (MSE) values in the temperature deviations from frictional heat, the disc’s thermo-mechanical characteristics are taken into account. Analysis of variance (ANOVA) is carried out using the data gathered from the DOE stage, we find 7 significant factors among the design variables. A meta-model using RSM is proposed for reduction of temperature deviations over the brake disc. An optimized brake pad is analyzed in terms of the temperature and thermal stress imparted on the brake disc, this optimized pad is then compared with the original pad. The maximum temperatures of the optimized pad and original pad were 399.8 °C and 480.6 °C, respectively. The thermal stress of the optimized pad and original pad were 640.4 MPa and 721.4 MPa, respectively. In the optimized model, the size of the hot band on the disc is larger than that from the original model, so the thermal stress distribution on the disc is smaller. Finally, the optimized pad was found to give significant performance benefits with a 16.8 % decrease in maximum temperature and 11.2 % decrease in thermal stress.